Response of Carex breviculmis to phosphorus deficiency and drought stress - Jiang, Songlin; Tang, Yiqing; Fan, Rong; Bai, Shidong; Wang, Xiaoqi; Huang, Yulin; Li, Weizhong; Ji, Wenli (Frontiers in Plant Science, 2023)
The drought and phosphorus deficiency have inevitably become environmental issues globally in the future. The analysis of plants functional trait variation and response strategies under the stress of phosphorus deficiency and drought is important to explore their ability to respond to potential ecological stress. In this study, Carex breviculmis was selected as the research object, and a 14-week pot experiment was conducted in a greenhouse, with two phosphorus treatment (add 0.5mmol/L or 0.05μmol/L phosphorus) and four drought treatment (add 0-5%Peg6000), totaling eight treatments. Biomass allocation characteristics, leaf anatomical characteristics, biochemical parameters, root morphology, chemical element content, and photosynthetic parameters were measured. The results showed that the anatomical characteristics, chemical elements, and photosynthetic parameters of Carex breviculmis responded more significantly to main effect of phosphorus deficiency. Stomatal width, leaf phosphorus content and maximum net photosynthetic rate decreased by 11.38%, 59.39%, 38.18% significantly (p<0.05), while the change in biomass was not significant (p>0.05). Biomass allocation characteristics and root morphology responded more significantly to main effect of drought. Severe drought significantly decreased leaf fresh weight by 61% and increased root to crown ratio by 223.3% compared to the control group (p<0.05). The combined effect of severe drought and phosphorus deficiency produced the highest leaf N/P ratio (291.1% of the control) to MDA concentration (243.6% of the control). Correlation analysis and redundancy analysis showed that the contributions of phosphorus and drought to functional trait variation were similar. Lower epidermal cell thickness was positively correlated with maximum net photosynthetic rate, leaf phosphorus, chlorophyll ab, and leaf fresh weight (p<0.05). In terms of response strategy, Carex breviculmis was affected at the microscopic level under phosphorus deficiency stress, but could maintain the aboveground and underground biomass well through a series of mechanisms. When affected by drought, it adopted the strategy of reducing leaf yield and improving root efficiency to maintain life activities. Carex breviculmis could maintain its traits well under low phosphorus and moderate drought, or better conditions. So it may have good ecological service potential in corresponding areas if promoted. This study also provided a reference for plant response to combined drought and phosphorus deficiency stresses.